Motion planning of rigid chain for rigid–flexible coupled robot. (2nd May 2018) - Wang, Keyi; Yin, Pengcheng; Yang, Haipeng; Wang, Lan
This work is motivated by the possibility that hemiplegic patients might achieve complete functional recovery of lower limb joints, muscles, and nerves by stretching and bending the lower limbs using rehabilitation training. A model of a rigid–flexible coupled lower limb rehabilitation robot is established and mechanically analyzed to satisfy both the control of various movement loci with flexion and extension and the requirements of rehabilitation training. According to the Denavit–Hartenberg method and the influence coefficient method, a kinematic model is established. Moreover, a static equilibrium equation is presented, and two motion planning methods for rigid branched chain movement are put forward. Fluctuation parameters are proposed to estimate the tension of every wire. A planning strategy of different rigid branched chains is analyzed during mechanical simulation using MATLAB [version 2013a]/SimMechanics along a specific trajectory. The law of wires and rigid branched chains is achieved. The wires' working performance of a parallel robot can be improved by introducing a rigid branched chain. During the dynamic simulation of the mechanism, other wires' tension changes are analyzed by setting the wire's tension (100 N) of a coupled branched chain. The wire's tension performance in the system is evaluated by its fluctuation performance. Finally, it is validated that the strategy of angle bisection is the best. The results prove that the rigid–flexible parallel rehabilitation robot can realize gait rehabilitation training of lower limbs, which leads to the servo control research of this robot.